ROLA PRZEJRZYSTOŚCI I ODPOWIEDZIALNOŚCI POLITYKI PIENIĘŻNEJ BANKU CENTRALNEGO - Musielak-Linkowska, Magdalena (Wydział Prawa i Administracji UAM, 2008)
The paper focuses on quality aspects of the monetary policy carried out by central banks, such as the recently emphasised transparency and democratic responsibility, and presents the role of such an institutionalised framework of the monetary policy in the communication strategy of central banks, its influence on the “perception” of the monetary policy by financial markets and the public, and the responsibility of relevant authorities for decisions made. Different types of transparencies and the manner in which democratic responsibility is interpreted have been characterised. Their links with the independence of contemporary central banks and the benefits flowing form a transparent monetary policy as well as consequences of a democratic responsibility on the monetary policy have been emphasised.
ROLE OF TRANSPARENCY AND RESPONSIBILITY IN THE MONETARY POLICY OF CENTRAL BANKS